Evaluation of the dynamic responses of truss spar platforms for different mooring materials in intact and damaged line conditions - Ahmed, M.O. (International Society of Offshore and Polar Engineers, 2019)
Considering the cost impact of mooring lines, it is essential to find the best possible line material and configuration for a given platform and metocean data, which can reduce responses to an acceptable level. Floating platforms installed in deepwaters experience severe environment and therefore, it is crucial they survive extreme events; primarily, when a mooring line is damaged. This paper addresses the performance evaluation of four mooring line materials in terms of dynamic responses of truss spar platforms for intact and damaged line conditions. Platform is modelled as a rigid body with three degrees-of-freedom and the dynamic response analysis is performed in time-domain. Mooring lines are modelled as massless springs and the stiffness is computed using quasi-static approach. It is observed that motions of platform about its mean position are nearly same for all mooring materials. Polyester mooring lines exhibited better performance in terms of restoring forces and mean position of platform for intact and damaged line conditions. In case of mooring line failure, the effect on mooring restoring performance and mean position of platform for different mooring materials is highest with polyester lines and least with steel wire lines. Â© 2019 by the International Society of Offshore and Polar Engineers (ISOPE).